A study on Process Safety Management (PSM) effectiveness based on human, technological and organizational factors in an oleochemical plant - Mohamad Ezuan, Abdul Jalil; Azizan, Ramli; Nurulain Athirah, Khairul Fahmi (Institution of Engineering and Technology, 2022)
Oleochemical industry produces chemical products such as fatty alcohols, methyl esters and glycerin. However, the industrial revolution increases the industry risk level to people and the environment. Their activities could result in risk of exposures to hazardous chemicals. The decay of process safety performance in most chemicals industries noticed in recent years are due to human, technological and organizational factors. Thus, this study intends to emphasize on the Process Safety Management (PSM) effectiveness based on these three factors. A total of 118 questionnaires were distributed, and 40 valid questionnaires were returned with response rate of 35%. Methods used to conduct this study were questionnaire, semi structured interview and field observation. Fourteen elements of process safety management (PSM) were identified. Strength, Weaknesses, Opportunities and Threat (SWOT) Analysis of PSM implementation based on human, technological and organizational factors in an oleochemical plant were identified. The level of effectiveness of PSM implementation survey was conducted using a questionnaire adapted from the United State Department of Energy Process Safety Management for Highly Hazardous Chemicals. The elements of PSM were analyzed by ranking all the mean score obtained for each element. The result revealed that the level of effectiveness for element of mechanical integrity was the highest (13.48) while the level of effectiveness for element of trade secret was the lowest (1.95).